Phased Ions‐Release Bilayer‐Guided Bone Regeneration Membrane with Nanostructure‐Mediated Antibacterial Adhesion - Liguo Zhang; Zhao Li; Yajing Fu; Haoyang Tian; Ting Wang; Hongrui Liu; Jianhua Li; Hong Liu; Shaohua Ge; Baojin Ma (Small Structures)
Bone defect repair involves a series of dynamic and complex processes, including immunoregulation, angiogenesis, and osteogenesis. Herein, a phased bioactive ions‐oriented release strategy is proposed to construct the bilayer Cu&Sr‐hydroxyapatite (HAp)/polylactic acid (CSHP‐)guided bone regeneration membrane. By harnessing distinct modes of ion delivery, Cu2+ adsorbed on the surface can be released quickly from the CSHP membrane to trigger a cascade of events including antibacterial reaction, regulating macrophage polarization, and enhancing angiogenesis. With the gradual degradation of HAp, Sr2+ doped in the lattice is sustainably released, synergistically regulating immunity, and encouraging the genesis of robust skeletal tissue. The bilayer structure of the CSHP membrane also ensures the oriented release of bioactive ions to the bone defect area, circumventing any systemic complications that might arise from indiscriminate dispersal. Furthermore, the nanoengineered HAp layer deters pathogenic colonization due to the low adhesion force, which can effectively prevent the formation of bacterial biofilms and infection after implantation. Overall, the multifunctional bilayer CSHP membrane, based on the phased and oriented ions release, adapts to the dynamic requirements of bone repair, thereby augmenting regeneration efficiency, and also providing a reference for the design of advanced repair materials.